Przymusowe leczenie psychiatryczne osób przyjętych do szpitala psychiatrycznego na zasadach określonych w ustawie z dnia 19 sierpnia 1994 r. o ochronie zdrowia psychicznego. Uwagi de lege lata i de lege ferenda - Pacian, Jolanta; Bartnik, Monika (PRAWO i WIĘŹ, 2026)
Admission to a psychiatric hospital and treatment of people with mental disorders are associated with temporary deprivation of liberty. This is why the prerequisites specified in the Mental Health Protection Act of 19.08.1994 determine strictly both the admission and stay of such people in psychiatric hospitals. A stay in a psychiatric hospital is an extremely difficult time for patients who are often subjected to compulsory treatment. The aim of the article is to present the legal regulations concerning the circumstances where a patient’s consent to psychiatric treatment is not necessary.